Preparation and Characterization of Bio-Based Freshness Indicator Labels Loaded with Natural Pigments with High Stability and Sensitivity - Yinglin Tan; Xiao Liu; Zhi Cheng; Qiping Zhan; Liyan Zhao (Foods)
Freshness indicator labels are crucial for food quality monitoring. However, existing labels often lack stability and sensitivity. This study aims to develop a safe freshness indicator label with high stability and sensitivity. By evaluating the pH response characteristics and stability of four natural pigments, purple potato anthocyanin (PA) was identified as having the best color properties. Mixing the more stable alizarin (AL) with PA improved the stability of the pigment solution without reducing sensitivity. These film labels are prepared with three natural biomolecules and polymers that are a two-by-two composite of them: soybean isolate protein, acacia bean gum, and sodium alginate. Through comparisons of ammonia response, color stability, water solubility, and mechanical properties, the soy protein isolate and locust bean gum composite were determined to be the optimal substrate system. The label of soybean protein isolate and locust bean gum was initially applied to the freshness identification of shrimp and chicken. The results show that the label can effectively respond to the spoilage of aquatic products and meat products and has great application potential in the field of food packaging.